Association genetics of chemical wood properties in black poplar (Populus nigra). Issue 1 (16th November 2012) - Guerra, Fernando P.; Wegrzyn, Jill L.; Sykes, Robert; Davis, Mark F.; Stanton, Brian J.; Neale, David B.
Summary: Black poplar ( Populus nigra ) is a potential feedstock for cellulosic ethanol production, although breeding for this specific end use is required. Our goal was to identify associations between single nucleotide polymorphism (SNP) markers within candidate genes encoding cellulose and lignin biosynthetic enzymes, with chemical wood property phenotypic traits, toward the aim of developing genomics‐based breeding technologies for bioethanol production. Pyrolysis molecular beam mass spectrometry was used to determine contents of five‐ and six‐carbon sugars, lignin, and syringyl : guaiacyl ratio. The association population included 599 clones from 17 half‐sib families, which were successfully genotyped using 433 SNPs from 39 candidate genes. Statistical analyses were performed to estimate genetic parameters, linkage disequilibrium (LD), and single marker and haplotype‐based associations. A moderate to high heritability was observed for all traits. The LD, across all candidate genes, showed a rapid decay with physical distance. Analysis of single marker–phenotype associations identified six significant marker–trait pairs, whereas nearly 280 haplotypes were associated with phenotypic traits, in both an individual and multiple trait‐specific manner. The rapid decay of LD within candidate genes in this population and the genetic associations identified suggest a close relationship between the associated SNPs and the causative polymorphisms underlying the genetic variation of lignocellulosic traits in black poplar.